Winckelmann and the invention of antiquity : history and aesthetics in the age of altertumswissenschaft - Harloe, Katherine, 1978- (Classical presences., 2013)
This volume provides a new perspective on the emergence of the modern study of antiquity, Altertumswissenschaft, in eighteenth-century Germany through an exploration of debates that arose over the work of the art historian Johann Joachim Winckelmann between his death in 1768 and the end of the century.